2015
DOI: 10.1002/hyp.10470
|View full text |Cite
|
Sign up to set email alerts
|

Deep drainage sensitivity to climate, edaphic factors, and woody encroachment, Oklahoma, USA

Abstract: Because groundwater is Earth's largest pool of freshwater, understanding the sensitivity of deep drainage to climate, soils, and land cover is critical in managing water resources. To better understand controls on this critical flux in the context of woody encroachment, we determined the sensitivity of deep drainage to climate, soil texture, soil compaction, rooting depth, growing season duration, and plant-water stress response using Hydrus-1D to simulate deep drainage. To evaluate the simulation results, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 54 publications
(75 reference statements)
0
17
0
1
Order By: Relevance
“…Similarly, changes in groundwater recharge in response to the expansion of rainfed cultivation in the Sahel, West Africa, were evaluated by Ibrahim et al (2014). Another related application is to anticipate the sensitivity of groundwater recharge to changes in climate in response to greenhouse effects (e.g., Leterme et al, 2012; Newcomer et al, 2014; Pfletschinger et al, 2014; Wine et al, 2015). Additional applications of HYDRUS for evaluating groundwater recharge are given below in the Groundwater Recharge Applications section and on the HYDRUS website.…”
Section: Selected Hydrus Applicationsmentioning
confidence: 99%
“…Similarly, changes in groundwater recharge in response to the expansion of rainfed cultivation in the Sahel, West Africa, were evaluated by Ibrahim et al (2014). Another related application is to anticipate the sensitivity of groundwater recharge to changes in climate in response to greenhouse effects (e.g., Leterme et al, 2012; Newcomer et al, 2014; Pfletschinger et al, 2014; Wine et al, 2015). Additional applications of HYDRUS for evaluating groundwater recharge are given below in the Groundwater Recharge Applications section and on the HYDRUS website.…”
Section: Selected Hydrus Applicationsmentioning
confidence: 99%
“…However, in addition to effecting modifications to climate forcings used in conventional physically based hydrologic predictions, climate change also effects ecological disturbances; these climatic controls on ecological disturbance may in turn be amplified by other components of global change (Dale et al 2001, Scheffer et al 2001. Widespread upland global change-induced ecological disturbances include woody encroachment (Van Auken 2000, Wine et al 2015), tree mortality due to pest-pathogen complexes (Kurz et al 2008), and wildfire (Westerling et al 2006). Assuming that these ecological disturbances can substantially influence Earth's future water balance, they represent structural uncertainties in the current approach to projecting future water resource availability.…”
Section: Introductionmentioning
confidence: 99%
“…Following the initial disturbance, the formerly forested system may be colonized by herbaceous plants having different functional traits than coniferous forest stands. During this vegetation recovery phase-conventionally referred to as secondary succession-shallower rooting depth and shorter growing season duration (in that order of importance) of herbaceous plants relative to evergreen trees may increase groundwater recharge, depending on interactions with transient climate (Wine et al 2015). Additionally, enhanced post-wildfire preferential flow may serve as another mechanism increasing groundwater recharge following wildfires (Stoof et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, despite the importance of soil factors in controlling Δ ET tree‐grass , climate is likely even more important than subsurface characteristics. Confirming the greater importance of climate compared to soil characteristics, Wine, Hendrickx, Cadol, Zou, and Ochsner () demonstrated that climate was more important than soil available water and rooting depth in determining deep drainage.…”
Section: Discussionmentioning
confidence: 94%